Efficient heat generation in large-area graphene films by electromagnetic wave absorption. (17th February 2017) - Kang, Sangmin; Choi, Haehyun; Lee, Soo Bin; Park, Seong Chae; Park, Jong Bo; Lee, Sangkyu; Kim, Youngsoo; Hong, Byung Hee
Abstract: Graphene has been intensively studied due to its outstanding electrical and thermal properties. Recently, it was found that the heat generation by Joule heating of graphene is limited by the conductivity of graphene. Here we suggest an alternative method to generate heat on a large-area graphene film more efficiently by utilizing the unique electromagnetic (EM) wave absorption property of graphene. The EM wave induces an oscillating magnetic moment generated by the orbital motion of moving electrons, which efficiently absorbs the EM energy and dissipate it as a thermal energy. In this case, the mobility of electron is more important than the conductivity, because the EM-induced diamagnetic moment is directly proportional to the speed of electron in an orbital motion. To control the charge carrier mobility of graphene we functionalized substrates with self-assembled monolayers (SAM). As the result, we find that the graphene showing the Dirac voltage close to zero can be more efficiently heated by EM waves. In addition, the temperature gradient also depends on the number of graphene. We expect that the efficient and fast heating of graphene films by EM waves can be utilized for smart heating windows and defogging windshields.